Browning mechanism and process optimization during MaizeMaize KX7349 Drying - Zhang, Chongxia; Yan, Xiaoping; Wu, Fang; He, Yang (Julius-Kühn-Archiv, 2018)
Browning of KX7349 maize during drying occurred mainly in the pericarp layer. Browning was caused by oxidation of water soluble matter in the pericarp layer. Moisture content had no significant influence on browning rate. Drying temperature, drying time and drying method (vacuum drying or hot-air drying) had significant influence on the browning rate. Through lab research, a prediction model for the relationship between browning rate and drying air temperature was developed. Total drying time is y=- 13.086+0.289X1+1.045X2, where y is the browning rate（%）, X1 is drying temperature（℃）, X2 is total drying time（h）, the value range of X1 was 30～80, the value range of X2 was 2～10. The concurrent and counter current dryer was applied in Nenjiang to optimize the drying process. The hot air temperature in each drying stage was reduced. When the hot air temperature of the 1st, 2nd, 3rd drying stage was reduced to 95℃,75℃,60℃ respectively, the browning rate was reduced to 15%～16%. Keeping the hot air temperature constant at each drying stage, by drying twice, the browning rate was reduced to 4%～6%.